PRESSING ISSUES OF EXPANDING AND INTERCONNECTING TRANSPORT CORRIDORS IN CENTRAL AND SOUTH ASIA (American Journal of Business Management, Economics and Banking, 2026)
This article analyzes the economic significance and current challenges of expanding transport corridors and enhancing integration processes between Central and South Asia. In the context of growing global trade volumes, reducing logistics costs, and deepening regional economic integration, the role of efficient transport infrastructure is becoming increasingly important. The study empirically evaluates the relationship between transport infrastructure development, trade volume, logistics efficiency, and gross domestic product growth.